An analysis of discriminatory actions found in 200 Pounds Beauty movie - Priska Natalia; Ahmad Muhid; Didit Kurniadi (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
This study aims to find the discriminatory actions in the 200 Pounds Beauty Movie. 200 Pounds Beauty is a 2006 film. This film tells the story of a fat woman named Hanna who wants to become a famous singer. However, because of her plump body, Hanna receives discriminatory treatment from other characters. Discrimination is the unfair treatment of a person or group of people who have differences in race, ethnicity, gender, and others. Therefore, the authors chose the film 200 Pounds Beauty to analyze the discriminatory treatment received by Hanna’s character. To be able to conduct research, the author uses a structural approach method. Then, the researchers collect data using the library research method and present the data collected in a sentence and pictures. From the research that has been done on the film 200 Pounds Beauty, it can be said that many of the acts of discrimination are accepted by Hanna’s character. Each discrimination that has been carried out has a different effect. The authors suggest that future researchers analyze discrimination more deeply.